(untitled) (INNOVATIVE ECONOMY, 2025)
Zhukovska A.Yu., Panasyuk V.M. INCLUSIVE MANAGEMENT: GENESIS OF EMERGENCE, TOOLS OF IMPLEMENTATION AND SOCIO-ECONOMIC EFFICIENCY Purpose. The aim of the article is to study the genesis of the concept of inclusive management, identify and systematize the mechanisms and tools for its implementation, and outline the directions for its effective application in modern organizations. Methodology of research. A historical-evolutionary approach was used to reconstruct the formation of the concept of inclusive management, structural-functional and comparative analysis (to identify the role and significance of inclusive-management mechanisms within organizational management systems), methods of classification and systematization (to compile the set of mechanisms and their corresponding toolkits) and analytical generalization (to develop phased recommendations). Findings. Based on the research results, the genesis of the concept of inclusive management was systematized; the theoretical and methodological prerequisites that determined its emergence and development, as well as the approaches to its further evolution, were outlined. The key mechanisms of inclusive management were identified: cross-cultural management, age management, gender-responsive management, talent management, case management, intersectional management, and universal design. Additionally, the system-forming role of universal design and the integrative function of intersectional management were substantiated. For each mechanism, its functional role within the inclusive management system and the tools for practical implementation were defined. On this basis, step-by-step recommendations for introducing inclusive management into the practice of modern organizations were formulated. Originality. For the first time, a model of the genesis and further development of the concept of inclusive management was developed, and a comprehensive classification of inclusive management mechanisms with defined functional roles and tools was proposed, enabling the integration of inclusivity principles into organizational management systems and enhancing their adaptability to modern challenges. Practical value. The research results can be applied in the management practice of organizations and public institutions to implement the principles of inclusivity and enhance management efficiency. Key words: inclusive management, mechanisms of inclusive management, universal design, intersectional management, gender-responsive management, talent management, case management, cross-cultural management, age management, socio-economic efficiency.